POLA ASUH ORANGTUA DALAM MEMBENTUK KARAKTER RELIGIUSITAS ANAK: STUDI KASUS KELUARGA MUSLIM - Kurniasari, Vani; Narulita, Sari; Wajdi, Firdaus (Mozaic : Islam Nusantara, 2022)
This research aims to describe and analyze the type of parenting style that dominates, as well as the support factors and the resisitance on the parent process of forming children’s religious character. This research describes the results of data from four families. The researcher uses qualitative descriptive method and a case study. In this research , the result shows that parenting that dominates in forming children's religious character is democratic parenting. Parents teach, familiarize, pay attention, and set a good example for children in performing the 5 daily prayers, reading The Holy Qur'an, Ramadan Fasting, good morals, studying, doing assignments, and being useful to others. Parents facilitate all the needs of children on their study. Supporting factors in the formation of children's religious character are parents following the pious people's behaviour, providing sustenance and halal food, parental involvement and sincerity in educating children, good parental communication relationships, conducive religious education environment, relation to pious people's houses, parents appreciating children's religious teachers, getting tahnik, parents' prayers and pious people', while the inhibiting factor is the difference of perception between parents and children due to differences in education in teaching children and the state of their hearts.